Molecular characterization of chromophobe renal cell carcinoma reveals mTOR pathway alterations in patients with poor outcome - Roldan-Romero, Juan María; Santos, María; Lanillos, Javier; Caleiras, Eduardo; Anguera, Georgia; Maroto, Pablo; García-Donas, Jesús; de Velasco, Guillermo; Martinez-Montes, Ángel Mario; Calsina, Bruna; Monteagudo, María; Letón, Rocío; et al. (Modern pathology, 2020)
Chromophobe renal cell carcinoma (chRCC) is a histologically and molecularly distinct class of rare renal tumor. TCGA studies revealed low mutational burden, with only TP53 and PTEN recurrently mutated, and discovered alterations in TERT promoter and in the electron transport chain Complex I genes. However, knowledge on drug targetable genes is limited and treatments at metastatic stage do not follow a molecular rationale. In a large series of 92 chRCC enriched with metastatic cases, we performed an in-depth characterization of mTOR pathway alterations through targeted NGS and immunohistochemistry (IHC) of phospho-S6, tuberin, and PTEN. Mutations in mitochondria, telomere maintenance and other renal cancer related genes and p53 IHC, were also assessed. The impact on metastasis development and disease specific survival was determined, using TCGA-KICH series (n = 65) for validation. mTOR pathway mutations (MTOR, TSC1, TSC2) were present in 17% of primary tumors, most of them being classified as pathogenic. Mutations were associated with positive IHC staining of phospho-S6 and PTEN (P = 0.009 and P = 0.001, respectively) and with chRCC eosinophilic variant (P = 0.039), supporting a biological relevance of the pathway. mTOR pathway mutations were associated with worse clinical outcomes. Survival analysis gave a hazard ratio of 5.5 (P = 0.027), and this association was confirmed in TCGA-KICH (HR = 10.3, P = 0.006). TP53 mutations were enriched in metastatic cases (P = 0.018), and mutations in telomere maintenance genes showed a trend in the same direction. p53 IHC staining pattern was associated with the underlying TP53 defect, and negative PTEN IHC staining (82% of cases) suggested PTEN loss as a chRCC hallmark. In conclusion, our study provides with novel genomic knowledge in chRCC and identifies novel markers of poor survival. Furthermore, this is the first study showing that mTOR pathway mutations correlate with poor prognosis, and may help to identify patients with increased sensitivity to mTOR inhibitors.